Emotional Labor, employee outcomes, support, and job autonomy: an empirical investigation of the hospitality industry in Sabah and the federal territory of Labuan - Ang, Magdalene Chooi Hwa; Rostinah Supinah; Minah Japang; Caroline Rosie Jeffrey Nasah (Universiti Malaysia Sabah, 2009)
The tourism industry in Sabah has been identified as one key sector to be promoted under the Sabah Development Corridor (SOC) Blue Print (2008-202S). The main objective of this plan is to promote the state as premier tourist destination. Given that, research should focus on the hospitality industry to provide managerial implications with regard to training and development of service workforce to empower them to provide world class service. One area worthy of empirical investigations is the performance of emotional labor as part and parcel of service work. The present study was thus undertaken to examine the process of emotional labor, operationalized as surface acting and deep acting, as performed by hotel workers in Sabah and the Federal Territory of labuan. The study also attempted to determine two consequences of performing emotional labor namely job satisfaction and emotional exhaustion. Further, it investigated the role of two organizational factors (i.e., support and job autonomy) in moderating these relationships. We employed a survey questionnaire to collect data from a total of 137 front-line hotel employees. To some extent, our findings are consistent with past findings in the west. Results revealed that women engaged more in deep acting as compared to men. Results also indicated that surface and deep acting significantly predicted employee outcomes in the proposed direction. Supervisory support, coworker support, and job autonomy served as moderators but only in some instances. Interestingly, the findings on the moderated relationships provided strong support for the notion of 'reverse buffering' (Beehr, 1995).